Clinical researchEffects of coenzyme Q10 supplementation on activities of selected antioxidative enzymes and lipid peroxidation in hypertensive patients treated with indapamide. A pilot study - Kędziora-Kornatowska, Kornelia; Czuczejko, Jolanta; Motyl, Jadwiga; Szewczyk-Golec, Karolina; Kozakiewicz, Mariusz; Pawluk, Hanna; Kędziora, Józef; Błaszczak, Robert; Banach, Maciej; Rysz, Jacek (Archives of Medical Science, 2010)
Introduction : An increase in oxidative stress is strongly documented in hypertensive patients. In blood vessels, oxidative stress increases the production of superoxide anion (O2•–) that reacts with nitric oxide (NO) and impairs the ability of endothelium to relax. Many reports indicate a beneficial effect of coenzyme Q10 (CoQ) in hypertension. Coenzyme Q10 therapy may lower O2•– and thus decrease the complications associated with hypertension. The aim of our study was to evaluate the effects of CoQ supplementation on antioxidative enzyme activities and lipid peroxidation in elderly hypertensive patients. Material and methods: We determined the activities of superoxide dismutase (SOD-1) and glutathione peroxidase (GSH-Px) and the concentration of malondialdehyde (MDA) in erythrocytes of 27 elderly (mean age 72.5 ±6.1 year) hypertensive patients treated with indapamide at baseline and after 12 weeks of CoQ supplementation (60 mg twice a day) in comparison with 30 healthy elderly volunteers (mean age 76.8 ±8.5 year). Results : Decrease of SOD-1 (p < 0.001) and insignificant reduction of GSH-Px activities and increase of MDA (p < 0.001) level were observed in hypertensive patients in comparison to healthy volunteers before supplementation. Coenzyme Q10 administration resulted in a significant increase only in SOD-1 activity (p < 0.001). Conclusions : The present study indicates that CoQ improves the most important component of the antioxidant defence system – SOD-1, which is responsible for O2•– scavenging. Coenzyme Q10 may be used as an additional therapeutic agent for prophylaxis and treatment of hypertension in elderly patients.